The Contribution of School Principal Leadership and School Culture to Teacher Performance - adrita gusdila; m giatman; jonni mardizal; riki mukhaiyar (JETL (Journal of Education, Teaching and Learning), 2025)
Teacher performance plays a crucial role in determining the quality of education. However, many schools continue to face challenges related to suboptimal teacher productivity, which may be influenced by leadership and cultural factors within the school environment. This study aims to examine the contribution of principal leadership and school culture to teacher performance. The research employed a quantitative approach using a correlational method. Data were collected from 80 teachers across several schools through structured questionnaires. The variables measured included principal leadership, school culture, and teacher performance. The data were analyzed using descriptive statistics, Pearson correlation, and multiple regression analysis. The results showed that both principal leadership and school culture had a strong and positive correlation with teacher performance, with correlation coefficients of 0.684 and 0.701, respectively. Furthermore, the regression analysis indicated that principal leadership and school culture together contributed significantly to teacher performance, with an R² value of 0.581. Among the two, school culture demonstrated a slightly higher influence than leadership. In conclusion, the findings suggest that enhancing both leadership practices and school culture can significantly improve teacher performance. It is recommended that school management prioritize the development of effective leadership strategies and the cultivation of a positive, collaborative school environment to support teacher growth and performance outcomes